IMPLEMENTASI MODEL PEMBELAJARAN PROJECT BASED LEARNING PADA MATERI SBDP KELAS 2 DI SD TAMBAKREJO 01 - Dwi Pamungkas Dwi; Choirul Huda; Aryo Andri Nugroho (STKIP Subang, 2023)
Education has an important role in shaping the future generations. Through education, people will acquire knowledge that can enhance critical thinking and develop social skills. In the world of education, student activity is an important factor in achieving effective learning. Student engagement refers to their active participation in the teaching and learning process, including participation in discussion, problem solving, collaboration and critical thinking. Based on the results of evaluating values ​​in the cognitive domain that researchers did in class II of SD Tambakrejo 01, namely the learning outcomes of SBdP in processing natural and artificial materials in work were still low. The purpose of this research is to analyze how the use of project-based learning models increases student activity. The subjects of this study were second grade students at SD Tambakrejo 01 Semarang City. The approach taken is a descriptive qualitative approach, carried out by presenting facts or data obtained from data sources. Data collection techniques through interviews, observation and documentation. The data analysis technique used consists of data acquisition, data reduction, data presentation and drawing conclusions. Based on the results of research at SDN Tambakrejo 01 class II, the results of learning evaluation using the PjBL model increased student activity in the learning process. The project-based learning model is able to influence the increase in student activity in learning. This research also really supports students to understand more deeply about the material presented. Student activity can also affect learning outcomes in the end.